Head-to-head comparison between echocardiography and cardiac MRI in the evaluation of the athlete's heart - Prakken, N. H. J.; Teske, A. J.; Cramer, M. J.; Mosterd, A.; Bosker, A. C.; Mali, W. P.; Doevendans, P. A.; Velthuis, B. K. (British Journal of Sports Medicine, 2012)
Objective Echocardiographic cut-off values are often used for cardiac MRI in athletic persons. This study investigates the difference between echocardiographic and cardiac MRI measurements of ventricular and atrial dimensions and ventricular wall thickness, and its effect on volume and wall mass prediction in athletic subjects compared with non-athletic controls.